Measurement of Objective Video Quality in Social Cloud Based on Reference Metric. (13th January 2020) - Karim, Sajida; He, Hui; Junejo, A. R.; Sattar, Mariyam
Abstract : This paper explores the objective of the present video quality analysis (VQA) and measures the full reference metrics keeping in view the quality degradation. During the research work, we conduct experiments on different social clouds (SCs) and low-quality videos. Selected videos are uploaded to SC to assess differences in video service and quality. WeChat shows that the average of all videos (Avg = 100), peak signal-to-noise ratio (PSNR), has no impact on other indicators. Therefore, we believe that WeChat provides the best video quality and multimedia services to their users to meet Quality of Service (QoS)/Quality of Experience (QoE).